New altitudinal record for brachycephalus actaeus monteiro, condez, garcia, comitti, amaral & haddad, 2018 (Anura, brachycephalidae), with comments on its habitats of occurrence - Bornschein, Marcos Ricardo [UNESP] (2019)
Brachycephalus actaeus Monteiro, Condez, Garcia, Comitti, Amaral & Haddad, 2018 is a recently described member of the B. pernix species group from northeastern Santa Catarina, southern Brazil, where it has been recorded from six localities at altitudes of 20–220 m. At the time of its description, this species was believed to be associated with lowlands, a unique trait for members of the B. pernix group. Here, we extend altitudinal distribution of B. actaeus to 530 m elevation and determine that the species occupies only montane forests.